A escassez do pensamento meditativo heideggeriano no contexto Iurdiano - Bernardo, Sarah Fernandes Santana (2018)
Meditative thinking, which thinks the sense of being and exactly for this reason, represents a space of greater intimacy, is proposed by Martin Heidegger as a counterpoint to the rational thinking, or as he calls it, calculative thinking. This calculative thinking, which is not restricted to calculations only, expresses the cybernetic mode that is always looking for the next opportunity, carried by the values of effectiveness, efficiency and performance results, that conquers the absolutism in the current season of planetary technique. Now, if the power, control and calculation, coming from Metaphysics, dominate the whole world how does it interfere with religion? Trying to understand the implications of the scarcity of meditation in religion, this research seeks to approach Heideggerian concepts as a key to the reading of the Iurdian context - Universal Church of the Kingdom of God. First presenting the Heideggerian perspective as a basis for the approximation of meditative thinking; then explaining the development of technique in theology, in order to understand the metaphysical tradition bequeathed to the Universal Church of the Kingdom of God; and finally, to raise three phenomena that reveal the meditative lacking in the Iurdian context